Sorghum stover as ruminant feed in Ethiopia: Effect of cultivar, site of growth, pre-harvest leaf stripping and storage on yield and morphology - Osafo, E.L.K.; Owen, E.; Said, A.N.; Gill, E.M.; McAllan, A.B.; Kebede, Y. (British Society of Animal Production, 1993)
Investigates the effect of cultivar and site of growing sorghum upon yield and composition of stover. Also studies the efects of pre-harvest leaf stripping and post-harvest storage.